SPIRIT ANGKA PADA BRANDNAME - Hartono Karnadi (Ars: Jurnal Seni Rupa dan Desain, 2008)
When numbers are applied as a merchandise brand, it is unique. There are many symbolic meaningscontained within. For several people, especially those who are involved in business, such an issue -"petungan" ("calculation" in the Javanese language) including feitg shui - is familiar. In this case, thenumbers mostly function to generate the spirit o f success.Keywords: number, brand, mystery, myth and spirit